2015
DOI: 10.1177/1947603515591628
|View full text |Cite
|
Sign up to set email alerts
|

Repairing Osteochondral Defects of Critical Size Using Multiple Costal Grafts

Abstract: Objective:To investigate the feasibility of repairing osteochondral defects of critical size by performing mosaicplasty using multiple sliced costal cartilage grafts, which enables repair of extensively injured knees using grafts from a single rib.Design:Critical osteochondral defects were prepared on the femoral groove of skeletally mature Japanese white rabbits. Costal cartilage grafts from a single rib were harvested and sliced into multiple segments (approximately 3-5 mm in length). The defects were left u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…Nevertheless, the pleural tear occurred accidentally due to the fragile pleural membrane [ 15 ]. Moreover, the pleura’s intimate attachment to the costochondral junction’s inner surface was observed [ 16 ]. However, the less traumatized costal cartilage harvesting technique was used to spare the perichondrial layer that reduced the donor site morbidity than the conventional method [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the pleural tear occurred accidentally due to the fragile pleural membrane [ 15 ]. Moreover, the pleura’s intimate attachment to the costochondral junction’s inner surface was observed [ 16 ]. However, the less traumatized costal cartilage harvesting technique was used to spare the perichondrial layer that reduced the donor site morbidity than the conventional method [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is anatomically evident that the rabbit’s pleural membrane is distinctly fragile [ 15 ]. According to Du et al [ 16 ], animal studies on the Japanese white male rabbits of 20 weeks of age discovered the reason for pleural injury during CCGs isolation; it was due to the intimate attachment of pleura to the inner surface of the rib around the costochondral junction [ 16 ]. Indeed, during an experimental study on rabbits, there is a chance of accidental exposure of the thoracic cavity and the penetrating injury to the pleural membrane.…”
Section: Introductionmentioning
confidence: 99%
“…IHC, although not as commonly used as the aforementioned stains, is also used for visualizing the distribution of specific extracellular matrix (ECM) components such as type I and II collagen. 23,28,45 In the case of osteochondral tissue regeneration, IHC can be a powerful method to visualize whether the regenerated cartilage is hyaline (majority type II collagen) or fibrous (type I collagen).…”
Section: Microctmentioning
confidence: 99%
“…Histological findings revealed that the intergraft gap between separated costal cartilage was filled by fibrous tissue, and the cleft between transplanted cartilage and host bone was interlinked by newly formed woven bone. 61 The junction and union between transplanted cartilage and recipient tissue is very important for functional recovery. 62 Alternatively, a cancellous iliac bone block could be isolated and implanted onto the surface of costal cartilage to yield an osteochondral complex.…”
Section: Costal Chondral/osteochondral Grafting In Animal Modelsmentioning
confidence: 99%